Tun Dr Mahathir's leadership patterns and the success story of Malaysia - Mohd Udin, Mashitah; Omar, Rusdi; Khamis, Kamarul Azman; Yusoff, Kamarul Zaman (The Mattingley Publishing Co., Inc., 2020)
Tun Dr Mahathir Mohamad came into power as the Prime Minister of Malaysia for the second time in May 2018. At 92, he was the eldest Head of Government in the world. His first term in Office was from 1981 to 2003, after which he resigned and handed the post to his deputy, Tun Abdullah Ahmad Badawi. This paper focuses on his leadership patterns and how they influenced Malaysia's development programmes and her foreign policy.Generally, leadership patterns refer to the leaders' behavioral patterns, and how these leaders construct their vision, mission and ideas for the development of their country apart from how to attract their followers. Good and honest leaders with high integrity are highly demanded in developing countries like Malaysia. Past research findings show that a country's leadership has strong influence on the country's socioeconomic progress and development. Tun Dr Mahathir's wisdom, high intellectual powers, leadership and management skills as well as his ways ofdoing things have impressed Malaysians, allowing them to trust and follow his instructions. He is a unique person with charismatic and effective leadership styles, apart from being an international relations expert. The writers feel that the Traits Theoryis a suitable approach to explain the leadership patterns shown by Tun Dr Mahathir. Some writers feel that personality is part of the traits concept thatdescribes a person who has natural similarities with the traits. The personality of an individual canactually be expressed in many ways, such as the gestures, physical activities, emotions, feelings, attitudes that can be seen over a period of time. As a leader, Tun Dr Mahathir feels that he must make decisions for his people, the results of these decisions will benefit all Malaysians at large. Many of Malaysian mega projects such as North-South Highway, Kuala Lumpur City Centre, Petronas Twin Towers, and the construction of Putrajaya, Cyberjaya and Kuala Lumpur International Airport and many other projects were initiated and completed during his era. Under his second term, Tun Dr Mahathir takes a more liberal and friendly approach to managing Malaysia's foreign policy.As trading nation, he wants Malaysia to be friendly to all, and enemy to none. He givestop priority to Malaysia's security to ensure that Malaysia's multiracial society can live in peace and harmony. After addressing the United Nations Assembly in 2018, he visited the United Kingdom. Tun Dr Mahathir later made visits to China, Japan, Russiaand Pakistan. In ASEAN region, he made official visits to Indonesia, Thailand, Philippines, Vietnam and Singapore to discuss trade and bilateral relationships. Malaysia and Singapore are actually very close neighbors, linked by a causeway and a bridge. Singapore gets much of its fresh water from Malaysia and many Malaysians work in Singapore. Tun Dr Mahathir knows this and handles such bilateral relationship wisely with high diplomacy where Malaysia-Singapore differences were settled through negotiations.